Similar Growth Performance but Contrasting Biomass Allocation of Root-Flooded Terrestrial Plant Alternanthera philoxeroides (Mart.) Griseb. in Response to Nutrient Versus Dissolved Oxygen Stress - Ayi, Qiaoli; Zeng, Bo; Yang, Kang; Lin, Feng; Zhang, Xiaoping; van Bodegom, Peter M.; Cornelissen, Johannes H. C. (Frontiers in Plant Science, 2019)
Terrestrial plants may experience nutrient and oxygen stress when they are submerged under the circumstance of climate change. It has been well reported that plants usually shift biomass allocation and produce more roots in response to nutrient deficiency. However, it is unclear whether plants experiencing oxygen deficiency stimulate biomass allocation to roots to enhance nutrient absorption, similar to how plants experiencing nutrient deficiency behave. We investigated the responses of the terrestrial species Alternanthera philoxeroides, upon root flooding, to nutrient versus dissolved oxygen deficiency in terms of plant growth, biomass allocation, root production, root efficiency (plant growth sustained per unit root surface area), and root aerenchyma formation. Both nutrient and dissolved oxygen deficiency hampered the growth of root-flooded plants. As expected, plants experiencing nutrient deficiency increased biomass allocation to roots and exhibited lower root efficiency; in contrast, plants experiencing dissolved oxygen deficiency decreased biomass allocation to roots but achieved higher root efficiency. The diameter of aerenchyma channels in roots were enlarged in plants experiencing dissolved oxygen deficiency but did not change in plants experiencing nutrient deficiency. The widening of aerenchyma channels in roots could have improved the oxygen status and thereby the nutrient absorption capability of roots in low oxygen environments, which might benefit the plants to tolerate flooding.